Lining prefabricated dowel(s) with fibre reinforced resin composite. (30th May 2016) - Aggarwal, Vivek; Singla, Mamta
Abstract: The study evaluated the adaptation and push‐out bond force of two different lined fibre dowels in oval canals. Dowel spaces were prepared in 30 obturated mandibular premolars with oval roots. The samples were divided into three groups ( n = 10). The first group received non‐lined fibre dowels (NL). The fibre dowels in the second group were lined with a resin composite (PL). The fibre dowels in third group were lined with resin composite reinforced with polyethylene fibre ribbon (PFL). The proportion of surface area (PSA) occupied by the dowel and push‐out bond force were analysed. The data were statistically analysed using two‐wayanova with post‐hoc Holm–Sidak and Tukey tests. The PSA was higher in lined dowels. Highest push‐out bond forces were recorded in PFL. Fibre reinforced composite lining improves the adaptation and push‐out bond force of fibre dowel in oval canals.